The VanS sensor negatively controls VanR-mediated transcriptional activation of glycopeptide resistance genes of Tn1546 and related elements in the absence of induction. - Arthur, M (1997)
Transposon Tn1546 from Enterococcus faecium BM4147 encodes a histidine protein kinase (VanS) and a response regulator (VanR) that regulate transcription of the vanHAX operon encoding a dehydrogenase (VanH), a ligase (VanA), and a D,D-dipeptidase (VanX). These last three enzymes confer resistance to glycopeptide antibiotics by production of peptidoglycan precursors ending in the depsipeptide D-alanyl-D-lactate. Transcription of vanS and the role of VanS in the regulation of the vanHAX operon were analyzed by inserting a cat reporter gene into vanS. Transcription of cat and vanX was inducible by glycopeptides in partial diploids harboring vanS and vanS(omega)cat but was constitutive in strains containing only vanS(omega)cat. Promoters P(R) and P(H), located upstream from vanR and vanH, respectively, were cloned into a promoter probing vector to study transactivation by chromosomally encoded VanR and VanS. The promoters were inactive in the absence of vanR and vanS, inducible by glycopeptides in the presence of both genes, and constitutively activated by VanR in the absence of VanS. Thus, induction of the vanHAX operon involves an amplification loop resulting from binding of phospho-VanR to the P(R) promoter and increased transcription of the vanR and vanS genes. Full activation of P(R) and P(H) by VanR was observed in the absence of VanS, indicating that the sensor negatively controls VanR in the absence of glycopeptides, presumably by dephosphorylation. Activation of the VanR response regulator in the absence of VanS may involve autophosphorylation of VanR with acetyl phosphate or phosphorylation by a heterologous histidine protein kinase.